Exploring Factors Affecting Students’ Difficulties in Learning Science at MTs Raudlatul ‘Uluum Aek Nabara Junior High School: Focus on Animal and Plant Reproduction Materials - Tasya Dhea Ananda; Rivo Hasper Dimenta; Rahmi Nazliah (Universitas Labuhanbatu, 2025)
The learning process is inseparable from internal and external obstacles experienced by individual students. When students fail to meet the established learning standards, we categorize them as learning difficulties. This study aims to analyze the factors of learning difficulties experienced by MTs Raudlatul ‘Uluum students in the science subject of animal and plant reproduction. Therefore, this research information will be an indicator in efforts to create conducive learning conditions and environments in this school. This study used a quantitative descriptive method with a total sampling technique. The data were collected using interviews, questionnaires, and documentation of student grades. In the study, it was found that students' learning problems are affected by their interest (88.56%), intelligence (81.22%), and health (78.29%); by social influences at school (78.02%); and by the method learning (77.45% with practicums and 73.93% with instruments). Learning difficulties faced by students who are in the puberty stage need attention so that the improvement of students' abilities, skills, and talents at school can be explored optimally